Pemetaan Sebaran Asal Siswa dan Klasifikasi Jarak Asal Siswa SMA Negeri di Kabupaten Pringsewu Menggunakan Metode Naive Bayes - Riska Aprilia; Kurnia Muludi; Aristoteles Aristoteles (Universitas Lampung, 2016)
Distance students can be seen from the data stored student's address. Address high school students in the Pringsewu District have different distances. This research was conducted to determine the classification of the distance stored in high school students in the Pringsewu District. Distance students are classified to obtain five categories: